Use of systemic therapy in the treatment of choroidal metastases from breast cancer. (26th November 2014) - Alzouebi, Mymoona; Ramakrishnan, Sundareswaran; Rennie, Ian; Salvi, Sachin
Abstract : This is a case report on the use of systemic therapy to successfully regress choroidal metastases due to breast cancer. The choroid is the commonest site for intraocular metastatic disease. Breast and lung cancer are frequently the primary malignancies. Traditionally, choroidal metastases are treated with local therapy to the eye including using either external beam radiotherapy, brachytherapy or, recently, with photodynamic therapy. We report on the impressive results obtained with the use of palliative paclitaxel chemotherapy and trastuzumab after only 8 weeks. Funduscopic images and ultrasound findings support this.